Transverse Schottky noise spectrum for bunches with space charge - O. Boine-Frankenheim; V. Kornilov (Physical Review Special Topics. Accelerators and Beams, 2009)
The effect of space charge and image currents on the transverse Schottky spectrum for bunched beams has been investigated using simulations combined with an analytic model. We found a good agreement between the shifts of synchrotron satellites observed in the simulation noise spectrum and a simplified model for head-tail modes with space charge and image currents.